The Hankel determinant associated with a singularly perturbed Laguerre unitary ensemble. Issue 1 (2nd January 2019) - Lyu, Shulin; Griffin, James; Chen, Yang
Abstract : We are concerned with the probability that all the eigenvalues of a unitary ensemble with the weight function, are greater than s . This probability is expressed as the quotient of Dn ( s, t ) and its value at s = 0, where Dn ( s, t ) denotes the determinant of the n dimensional Hankel matrices generated by the moments of w ( x ; t ) on x ∈ [ s, ∞). In this paper we focus specifically on the Hankel determinant Dn ( s, t ) and its properties. Based on the ladder operators adapted to the monic polynomials orthogonal with respect to w ( x ; t ), and from the associated supplementary conditions and a sum-rule, we show that the log-derivative of the Hankel determinant, viewed as a function of s and t, satisfies a second order sixth degree partial differential equation, where n appears as a parameter. In order to go to the thermodynamic limit, of infinitely large matrices, we envisage a scenario where n → ∞, s → 0, and t → 0 such that S := 4 ns and T := (2 n + 1 + α ) t are finite. After such a double scaling, the large finite n equation reduces to a second order second degree equation, in the variables S and T, from which we derive the asymptotic expansion of the scaled Hankel determinant in three cases of S and T : S → ∞ with T fixed, S → 0 with T > 0 fixed, and T → ∞ with S > 0 fixed. The constant term in the asymptotic expansion is shown to satisfy a difference equation and one of its solutions is the Tracy-Widom constant.